2014
DOI: 10.15376/biores.10.1.227-239
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Rheological Properties of Rice Husks Treated by Composting Process

Abstract: A composting treatment was employed in an effort to improve the processability of rice husks. Changes in the chemical composition, physical structure, and rheological properties of modified rice husks were analyzed. The results indicated that the average diameter of composttreated samples was significantly higher than that of the untreated samples because they were able to adhere to each other by the bacterial protein. Scanning electron microscopy images showed that the epidermis became rugged and lumpy becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…The distributions of lignocellulose components in sawdusts were similar and consistent with previously reported values [43]. Rice husk composition was in line with other reports: 25-40% cellulose, 8-21% hemicellulose, 15-31% lignin, 15-17% ash and waxes, 2-8% other soluble substances and up to 3% proteins [44,45]. Particularly, Costa et al [46] studied the contents of the lignocellulosic components of zoita sawdust to evaluate its potential as a pyrolysis raw material and reported 23.5 %wt.…”
Section: Composition Of Raw Biomassessupporting
confidence: 92%
“…The distributions of lignocellulose components in sawdusts were similar and consistent with previously reported values [43]. Rice husk composition was in line with other reports: 25-40% cellulose, 8-21% hemicellulose, 15-31% lignin, 15-17% ash and waxes, 2-8% other soluble substances and up to 3% proteins [44,45]. Particularly, Costa et al [46] studied the contents of the lignocellulosic components of zoita sawdust to evaluate its potential as a pyrolysis raw material and reported 23.5 %wt.…”
Section: Composition Of Raw Biomassessupporting
confidence: 92%
“…Previous research found that rice husks had moisture content of 9.5%, 48.1% of total carbon, 0.78% nitrogen total (Wu et al, 2015), and C/N ratio at 73.4 (Bian et al, 2019). As shown in Table 1, teak (Tectona grandis) wood scraps sample displayed a relatively similar character with rice husks, except C/N ratio.…”
Section: Results and Discussion Rice Husks And Teak Wood Scraps Charamentioning
confidence: 81%
“…micro-organismos que são capazes de produzir enzimas celulases e às xilases que degradam a celulose e a hemicelulose (Wu et al, 2015). Maior teor de lignina (Tabela 5) foi verificado quando utilizado dejeto de suínos (9,40%) e menor com dejeto de bovinos (7,2%), tanto em compostagem quanto em vermicompostagem.…”
Section: Resultsunclassified